2008
DOI: 10.2175/106143007x221283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Suburban Land Use on Phosphorus Fractions and Speciation in the Upper Peruque Creek, Eastern Missouri

Abstract: This field study was conducted to explore the spatial and seasonal changes in total phosphorus and fraction distribution in relation to land uses. Water samples were collected biweekly at four sampling locations, which represented different potential phosphorus sources along the Upper Peruque Creek in Eastern Missouri. Total phosphorus concentrations of .0.8 mg/L appeared sporadically at site 2, downstream of a small community, with an average of 0.82 6 0.14 mg/L in fall. Particulate phosphorus accounted for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the last decade inositol phosphates have mostly been identified in sediments using 31 P NMR spectroscopy on NaOH-EDTA sediment extracts; although there has been at least one study that used XANES. [13] Interestingly, in one study, inositol phosphates could be detected using high field mass spectroscopy, but not 31 P NMR spectroscopy. [68] Relative to sediments, there have been far fewer studies of inositol phosphates in the water column.…”
Section: Identificationmentioning
confidence: 94%
See 2 more Smart Citations
“…In the last decade inositol phosphates have mostly been identified in sediments using 31 P NMR spectroscopy on NaOH-EDTA sediment extracts; although there has been at least one study that used XANES. [13] Interestingly, in one study, inositol phosphates could be detected using high field mass spectroscopy, but not 31 P NMR spectroscopy. [68] Relative to sediments, there have been far fewer studies of inositol phosphates in the water column.…”
Section: Identificationmentioning
confidence: 94%
“…De Groot and Golterman [64] estimated that inositol phosphates represented between 3 and 22.5 % (mean ¼ 11.5 %) of the total sedimentary P in sediments of the Camarge, whereas Keller et al, [13] using XANES spectroscopy, found that inositol phosphates accounted for 15 and 29 % of the total P in two sediment samples from a creek in the upper reaches of the Mississippi River; however much lower concentrations have been found elsewhere. For example both Turner and Newman [73] and Cheesman et al [74] were unable to detect IHPs in a series of natural and constructed Florida wetlands.…”
Section: Quantificationmentioning
confidence: 99%
See 1 more Smart Citation